PENTINGNYA LITERASI SYARIAH DALAM MENYELARASKAN KEUANGAN KELUARGA DI DESA MEDALKRISNA - Tias, Elsa Ayuning; Rahmawati, Rafika; Mardiah, Siti; Khoiriyah, Ummi (LPPM Universitas Islam 45, 2024)
It is difficult for some communities to obtain corporate funding under these conditions, due to a lack of financial literacy and uneven distribution of financial institutions. In addition, the low level of literacy and understanding of the community contributes to the community's decision to borrow money from Bank Emok. The community service team used the community education method in conducting education or socialization to residents of Medalkrisna Village, Bojongmangu Subdistrict in an effort to improve communication on the importance of Sharia literacy in harmonizing family finances. The results of community service to the local community show that the community understands more about financial literacy and understands the dangers of Bank Emok so that the local community is interested in switching to using Sharia Banks.